Navigating Online Platform Oversight: The Role and Challenges of Indonesia Business Competition Supervisory Commission - Riskayanti (Jurnal Mulawarman Law Review, 2024)
This research aims to analyzes how digital transformation impacts the behaviors of online platforms, which presents challenges for competition law. The business strategies and behavior of online platforms have raised concerns about their negative effects on the competitive landscape. These concerns include the legality of such practices and the necessity of specific regulatory measures. The research method is normative legal research with a conceptual approach, which involves identifying and analyzing legal issues and providing solutions. Based on the legal analysis, the results showed that the Business Competition Supervisory Commission (KPPU) faces challenges in regulating online platforms. These challenges consist of the regulatory challenges that must be addressed include the inadequate preparation of competition authorities, the influence of Indonesian culture on market behavior, and the substance of rules. Therefore, it is crucial for KPPU to properly navigate online platforms by establishing sui generis rules within the competitive landscape. In the context of a competitive business landscape, it is imperative to ensure oversight of online platforms, particularly given the preeminent position of this business model within the Indonesian market.